TALK SHOW KESEHATAN PENGGUNAAN OBAT YANG BAIK DAN BENAR - Dwi Kurniawati Sambodo; Yuli Nurullaili Efendi (Jurnal Abdi Masyarakat Kita, 2021)
One study was showed that about 50% of patients did not use the medicine correctly, did not regularly, or stopped the medichine prematurely. The most common causes are medicine’s effects, the patient did not feel the benefit of the medicine, or a complicated method of use. According to Anief (1997), although drugs can heal, there are many instances that a person has suffered from medicine poisoning. Therefore it can be said that medicine can be medicinal and also poisonous. Through this activity, it is hoped that there will be an increase in public knowledge about how to use medicine that are effective and safe, and that people can do DAGUSIBU properly. The material presented during this event was the definition of medicine, tips on how to get and use drugs effectively and safely, and the drug DAGUSIBU. The health talk show for the use of effective and safe medicine as expected. seen from the participants who attanded and the enthusiasm of the participants in participating in the talk show.